Feasibility of biomarkers to measure stress, burnout and fatigue in emergency nurses: a cross-sectional study - Frederick R Walker; Natasha Weaver; Kerry J Inder; Lucinda M Mithen (BMJ Open, 2023)
Introduction Retaining nurses in the workforce is an urgent concern in healthcare. Emergency nurses report high levels of stress and burnout, however, there is no gold standard of how to measure these responses. This study aims to measure stress, burnout, and fatigue in emergency nurses using biomarkers and psychometric instruments. Biomarkers will be used to better understand nurses’ levels of stress and burnout and to assess the feasibility of using biomarkers as a viable stress measurement tool in a real-world setting.Methods and analysis A two stage cross-sectional design to measure stress, burnout and fatigue in emergency nurses while they work is proposed. All registered and enrolled nurses working in the emergency department from four hospitals in Australia will be invited to participate. Validated psychometric tools will be used in stage 1 to measure depression, anxiety, acute stress, chronic stress, burnout and fatigue. Biomarkers comprising hair cortisol, saliva alpha amylase and heart rate variability will be collected as an objective measure of stress and burnout in stage 2 over one working shift per participant. Written consent will be sought for stage 2 where nurses will provide one hair sample, wear a heart rate sensor and be asked to collect their saliva at three different time points of one shift. Data analysis will measure the domains of acute stress, chronic stress and burnout and explore relationships and correlation between psychometric measures and biomarkers.Ethics and dissemination Ethics approval obtained from the Human Research Ethics Committee of the Hunter New England Local Health District (approval number: HREC/2020/ETH01684) and University of Newcastle HREC (H-2022-0169). Results will be reported in peer-reviewed publications using the Strengthening the Reporting of Observational Studies in Epidemiology guidelines. Public dissemination will occur by presenting at conferences and to the participating local health district.